Effectiveness of a scalable group-based education and monitoring program, delivered by health workers, to improve control of hypertension in rural India: A cluster randomised controlled trial. - Dilan Giguruwa Gamage; Michaela A Riddell; Rohina Joshi; Kavumpurathu R Thankappan; Clara K Chow; Brian Oldenburg; Roger G Evans; Ajay S Mahal; Kartik Kalyanram; Kamakshi Kartik; Oduru Suresh; Nihal Thomas; et al. (PLoS Medicine)
Background New methods are required to manage hypertension in resource-poor settings. We hypothesised that a community health worker (CHW)-led group-based education and monitoring intervention would improve control of blood pressure (BP). Methods and findings We conducted a baseline community-based survey followed by a cluster randomised controlled trial of people with hypertension in 3 rural regions of South India, each at differing stages of epidemiological transition. Participants with hypertension, defined as BP ≥ 140/90 mm Hg or taking antihypertensive medication, were advised to visit a doctor. In each region, villages were randomly assigned to intervention or usual care (UC) in a 1:2 ratio. In intervention clusters, trained CHWs delivered a group-based intervention to people with hypertension. The program, conducted fortnightly for 3 months, included monitoring of BP, education about hypertension, and support for healthy lifestyle change. Outcomes were assessed approximately 2 months after completion of the intervention. The primary outcome was control of BP (BP < 140/90 mm Hg), analysed using mixed effects regression, clustered by village within region and adjusted for baseline control of hypertension (using intention-to-treat principles). Of 2,382 potentially eligible people, 637 from 5 intervention clusters and 1,097 from 10 UC clusters were recruited between November 2015 and April 2016, with follow-up occurring in 459 in the intervention group and 1,012 in UC. Mean age was 56.9 years (SD 13.7). Baseline BP was similar between groups. Control of BP improved from baseline to follow-up more in the intervention group (from 227 [49.5%] to 320 [69.7%] individuals) than in the UC group (from 528 [52.2%] to 624 [61.7%] individuals) (odds ratio [OR] 1.6, 95% CI 1.2-2.1; P = 0.001). In secondary outcome analyses, there was a greater decline in systolic BP in the intervention than UC group (-5.0 mm Hg, 95% CI -7.1 to -3.0; P < 0.001) and a greater decline in diastolic BP (-2.1 mm Hg, 95% CI -3.6 to -0.6; P < 0.006), but no detectable difference in the use of BP-lowering medications between groups (OR 1.2, 95% CI 0.8-1.9; P = 0.34). Similar results were found when using imputation analyses that included those lost to follow-up. Limitations include a relatively short follow-up period and use of outcome assessors who were not blinded to the group allocation. Conclusions While the durability of the effect is uncertain, this trial provides evidence that a low-cost program using CHWs to deliver an education and monitoring intervention is effective in controlling BP and is potentially scalable in resource-poor settings globally. Trial registration The trial was registered with the Clinical Trials Registry-India (CTRI/2016/02/006678).